2003
DOI: 10.1002/acp.876
|View full text |Cite
|
Sign up to set email alerts
|

Variations on a technique: enhancing children's recall using narrative elaboration training

Abstract: The current study examined first, whether the positive effects demonstrated by the Narrative Elaboration Technique (NET) could be further enhanced when coupled with mental reinstatement of context (MR), prior to interview, and second, compared the efficacy of the NET at a two-week delay and a nine-month delay. In Study 1, 47 children took part as a class in a staged event about safety. Two weeks later they received a single training session, and the following day were interviewed with either the NET (n ¼ 16), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 58 publications
3
41
1
Order By: Relevance
“…In analogue contexts, the NET appears to help children provide more complete and equivalently accurate event reports (e.g. Brown & Pipe, 2003a, 2003bDorado & Saywitz, 2001). Further, Camparo, Wagner, and Saywitz (2001) reported that children trained and interviewed using the NET were not disproportionately likely to talk about a fictitious event although some children attempted to describe this non-event during prompted recall or specific questioning when their initial denials of the event were ignored.…”
Section: Probing Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…In analogue contexts, the NET appears to help children provide more complete and equivalently accurate event reports (e.g. Brown & Pipe, 2003a, 2003bDorado & Saywitz, 2001). Further, Camparo, Wagner, and Saywitz (2001) reported that children trained and interviewed using the NET were not disproportionately likely to talk about a fictitious event although some children attempted to describe this non-event during prompted recall or specific questioning when their initial denials of the event were ignored.…”
Section: Probing Memorymentioning
confidence: 99%
“…Interestingly, several researchers have shown that the gains associated with the NET can be obtained simply by providing verbal prompts for the same categories of information cued using the NET cue cards, without training in how to talk about the past (Bowen & Howie, 2002;Brown & Pipe, 2003a, 2003bElischberger & Roebers, 2001). In other words, simply asking children to report what they saw and heard (Poole & Lindsay, 1995) or to talk about different categories of information (Quas et al, 2000) can produce increases in the amounts of information reported.…”
Section: Probing Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Adults may inadvertently or deliberately inXuence the responses given by children through their questioning techniques. Many researchers have outlined the eVect of explicit suggestive techniques, such as the use of leading questions, the number of interviews, and the use of props, as well as the best ways in which to obtain accurate recall (Alexander et al, 2002;Brown & Pipe, 2003;Coxon & Valentine, 1997). But there are also other factors that can inXuence children's responses in interviews, including the eVects of repeated questioning.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on preschoolers because, compared with older children, younger children are more vulnerable to maltreatment (U.S. Department of Health and Human Services, 2013) and tend to provide less complete memory reports (Pipe et al, 2004). As alluded to earlier, with only a few exceptions (Dorado & Saywitz, 2001;Kulkofsky, 2010), most previous studies have tested the effects of the NET or the verbal labels procedure with school-aged children (e.g., Brown & Pipe, 2003a,2003bCamparo et al, 2001;. The present study aimed to extend evidence of the generalizability of the verbal labels procedure with 3-to 5-year-olds, with the prediction that it would facilitate the completeness and accuracy of young children's event memory.…”
mentioning
confidence: 99%